1985
DOI: 10.1161/01.hyp.7.6.923
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of acute hypercalcemic hypertension in the conscious rat.

Abstract: SUMMARY Acute hypercalcemia in the conscious, unanesthetized rat, achieved by a 30-minute infusion of CaCl 2 (serum calcium level, 12.8 ± 0.6 mg/dl) resulted in significant elevation of mean arterial pressure (from 112 ± 2 mm Hg to 129 ± 3 mm Hg, p < 0.001). This pressor response was associated with a significant increase in systemic vascular resistance, from 0.45 ± 0.02 mm Hg/(ml/min)/kg body weight to 0.50 ± 0.02 mm Hg/(ml/min)/kg body weight (p < 0.05), but it caused no alteration in cardiac index. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

1987
1987
1995
1995

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
2
13
2
Order By: Relevance
“…Previous studies in our lab oratory have shown that acute hypercalcemia causes a dose-related rise in blood pressure. However, we also showed that increases in serum calcium in the order of magnitude used in the present study were not associated with any significant change in blood pressure [3], In addi tion. evidence is available in animals and in man that subpressor doses of calcium cause no changes in cardiac out put or in systemic vascular resistance, whereas pressor 90 Liu/Bigazzi/Ballard/Campese Hypercalcemia and RSNA * p < 0.05 (Anova) compared to rats given calcium or a-methyltyrosine.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies in our lab oratory have shown that acute hypercalcemia causes a dose-related rise in blood pressure. However, we also showed that increases in serum calcium in the order of magnitude used in the present study were not associated with any significant change in blood pressure [3], In addi tion. evidence is available in animals and in man that subpressor doses of calcium cause no changes in cardiac out put or in systemic vascular resistance, whereas pressor 90 Liu/Bigazzi/Ballard/Campese Hypercalcemia and RSNA * p < 0.05 (Anova) compared to rats given calcium or a-methyltyrosine.…”
Section: Discussionsupporting
confidence: 50%
“…34 In another study, 30 the mean blood pressure increment in Wistar rats given a much larger calcium load was only +12 mm Hg (112±3->124±5 mm Hg) despite a serum calcium that was twice that of the Sprague-Dawley rats (24.9±1.2 mg/dl). This suggests that the pressor responsiveness to hypercalcemia is blunted in Wistar rats.…”
Section: Figure 2 Bar Graph Of Plasma Atrial Natriuretic Factor (Anpmentioning
confidence: 94%
“…17 Acutely induced hypercalcemia in conscious rats causes hypertension and is reported to be without any involvement of catecholamines. 33 Other reports, however, indicate that catecholamines are involved in hypertension induced by hypercalcemia. 13 ' l6 -M Our laboratory has reported that dietary calcium deficiency does not alter the noradrenergic response of atria in rats, 33 but vitamin D deficiency does.…”
Section: Figure 2 Depressor Response To Parathyroid Hormone (Pth-[1 mentioning
confidence: 99%
“…33 Other reports, however, indicate that catecholamines are involved in hypertension induced by hypercalcemia. 13 ' l6 -M Our laboratory has reported that dietary calcium deficiency does not alter the noradrenergic response of atria in rats, 33 but vitamin D deficiency does. We believe that when more studies are done a clear picture of catecholamine involvement will emerge.…”
Section: Figure 2 Depressor Response To Parathyroid Hormone (Pth-[1 mentioning
confidence: 99%
See 1 more Smart Citation